Determinan Demografi Penggunaan Internet Petani Padi di Indonesia dan Kaitannya Dengan Produktivitas - Kadir Kadir; Octavia Rizky Prasetyo (Seminar Nasional Official Statistics, 2021)
This study aims to identify the demographic determinants of internet use on paddy farmers in Indonesia and the link of the usage to the paddy yield cultivated by the farmers. A logistic regression model implemented on the enumeration results of the Intercensal of Agricultural Survey (SUTAS) carried out by Statistics Indonesia (BPS) in 2018 found that internet use among the paddy farmers is a phenomenon of young farmers, well educated, men and residents of Java Island. Unfortunately, paddy farmers with those combined demographic characteristics only represent a small fraction of the total paddy farmers in Indonesia. This study also pointed out that there is a statistically significant difference in the yield of paddy cultivated by farmers using the internet and non-users. The average yield of internet users is significantly higher than that of non-internet users. This finding is a strong indication that internet use by paddy farmers could have a significant impact on the increase of paddy yield cultivated.